1987
DOI: 10.1148/radiology.163.2.3562824
|View full text |Cite
|
Sign up to set email alerts
|

Dural fistulas involving the transverse and sigmoid sinuses: results of treatment in 28 patients.

Abstract: Twenty-eight symptomatic dural fistulas involving the transverse and sigmoid sinuses were treated between 1978 and 1986 with a variety of treatment modalities. Occipital artery compression therapy resulted in a complete cure in two of nine patients (22%) and improvement in three of nine (33%). There were no complications from this treatment. Patients who were excluded or in whom compression therapy failed were treated with embolization alone or in conjunction with surgery. Of the 17 patients who underwent embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(64 citation statements)
references
References 0 publications
0
61
0
3
Order By: Relevance
“…3,11) Temporary occlusion of the arterial supply by the maneuver technique is often used as a treatment for dural AVF, and repeated temporary occlusion of the occipital artery resulted in improvement in 5 of 9 cases of transverse dural AVF. 6) These results suggest that temporary stagnation of blood flow might promote the spontaneous occlusion of dural AVFs. An interesting theory for the development of dural AVFs is based on the findings that changes of the intradural multiple arterial channels affect the sinus thrombosis and promote the development of dural AVFs.…”
Section: Discussionmentioning
confidence: 88%
“…3,11) Temporary occlusion of the arterial supply by the maneuver technique is often used as a treatment for dural AVF, and repeated temporary occlusion of the occipital artery resulted in improvement in 5 of 9 cases of transverse dural AVF. 6) These results suggest that temporary stagnation of blood flow might promote the spontaneous occlusion of dural AVFs. An interesting theory for the development of dural AVFs is based on the findings that changes of the intradural multiple arterial channels affect the sinus thrombosis and promote the development of dural AVFs.…”
Section: Discussionmentioning
confidence: 88%
“…In some studies, transvenous embolization using coils for curative purposes has been demonstrated to be very effective (complete occlusion in 80%-100% of cases) or anatomic and clinical cure rates of 71%-89% and 77%-96% in cDAVF cases, respectively 8,21,22 . However, serious complications associated with vascular damage and intracranial hemorrhage have also been reported 8,23 .…”
Section: Discussionmentioning
confidence: 99%
“…If once again no lesion is found, repeat angiography is indicated, including visualization of the external carotid artery because branches of this artery can be the main or the sole feeders.53 Rebleeding may occur in patients with dural AVMs; in a series of 28 patients, 5 presented with subarachnoid hemorrhage, and 3 of these 5 had one or more rebleeds. 54 …”
Section: Dural Arteriovenous Malformationmentioning
confidence: 99%